Evaluasi Sistem Struktur Beton Pracetak Untuk Meningkatkan Kinerja Bangunan Tingkat Tinggi: Studi Kasus Proyek Gkt-Pik2 - M. Daud Utomo; Suryawan Murtiadi; Syahril Taufik (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The rapid development of the construction industry demands optimization in efficiency and sustainability principles. One approach that is increasingly being considered to address these challenges is the utilization of precast concrete systems. This research evaluates the impact of precast concrete structural system implementation on project performance, with a case study on the Kemah Tabernakel Church project in Pantai Indah Kapuk 2 (GKT-PIK2). Many factors can affect the performance of construction projects, including the 5M+T factors: Man, Measurement, Method, Material, Machine, and Time. The research uses a descriptive qualitative approach combined with quantitative analysis thru field observation, distribution of Likert-scale questionnaires, and expert interviews. Data analysis is performed using correlation tests and multiple linear regression with SPSS software to determine the significance of the impact of precast concrete structure system implementation. The research results indicate that the implementation of the precast system has a significant impact on improving project performance. The five dominant variables affecting performance are design changes, workforce competency, installation methods, tower crane usage, and timely delivery. These five factors have been proven to have a positive and linear relationship with overall project performance achievement. This research concludes that a precast concrete structural system designed according to SNI 9163:2023 regulations, and supported by appropriate technical and managerial strategies, is capable of improving project execution performance. The contribution of this research also provides practical implications in the form of technical recommendations to support the successful implementation of precast systems in multi-story building construction projects.